Novel targeted therapies in chronic myeloid leukemia - Muhammad Sameer Ashaq; Qian Zhou; Zhuoran Li; Baobing Zhao (Elsevier, 2024)
Chronic myeloid leukemia (CML) is the chronic proliferation of myeloid-lineage cells in hematopoietic stem cells driven by the BCR-ABL1 fusion oncoprotein. The development of tyrosine kinase inhibitors (TKIs) has revolutionized CML treatment; however, resistance and intolerance to these drugs remain key challenges. CML stem cells (CMLSCs) are the root cause of CML relapse and resistance to TKIs. This review discusses novel targeted therapeutic options targeting CMLSCs to address the abovementioned challenges. Numerous novel TKIs, such as flumatinib, vodobatinib, and olverembatinib, have shown remarkable potential against BCR-ABL1, but few, including AT9283, MK0457, and DCC-2036, are still undergoing clinical trials. Targeting CMLSCs is a fundamental therapeutic approach for the treatment of CML progression, relapse, and TKI resistance. In this review, novel agents targeting core signaling pathways and novel molecular targets in CMLSCs are highlighted. Currently, multiple approaches, such as targeting epigenetic modifications or microRNAs and altering metabolism in leukemic cells, have shown desirable effects in treating CML. Immunotherapy, autophagy inhibitors, and protein synthesis inhibitors are novel and effective therapies for the treatment of CML. Although various therapeutic strategies have provided exceptional results in the treatment of CML, the challenges of TKI resistance and CML remission or relapse remain. Therefore, current therapeutic approaches and targeted therapies have practical and clinical implications for achieving desirable outcomes.